3D-Visualization of Neurovascular Compression at the Ventrolateral Medulla in Patients with Arterial Hypertension - Manava, Panagiota; Naraghi, Ramin; Schmieder, Roland; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael M.; Buchfelder, Michael; Hastreiter, Peter (Clinical Neuroradiology, 2020)
Purpose: Controversy exists on the association of arterial hypertension (HTN) and neurovascular compression (NVC) at the ventrolateral medulla (VLM). No standardized and reproducible technique has been introduced yet for detection of NVC in HTN. This study aimed to generate, analyze and compare different results of exact reproducible anatomical 3D-representations of the VLM in patients with HTN, based on magnetic resonance imaging (MRI). Methods: A 3T scanner provided MRI (T2-constructive interference in steady state (CISS) high resolution imaging and three-dimensional Time-of-flight (3D-TOF) angiography) from the posterior fossa of 44 patients with clinical treatment-resistant HTN. Image processing consists of segmentation of the CISS data, registration and fusion of the CISS and TOF data and visualization. For each patient two 3D-visualizations (before and after fusion) were obtained. The reproduction quality of the vessels, flow-related signal variability and pulsation artifacts were analyzed and compared, using a ranking score. Results: Integrating vascular information from TOF into CISS data reduced artifacts in 3D-visualizations of exclusively processed CISS data. The quality of 3D-visualization of the vessels near the brain stem was significantly improved (p = 0.004). The results were reproducible and reliable. The quality of the 3D-presentations of neurovascular relationships at the VLM improved significantly (p < 0.001). Conclusion: The 3D-visualization of fused image data provides an excellent overview of the relationship between cranial nerves and vessels at the VLM and simplifies the detection of NVC in HTN. It provides a powerful tool for future clinical and scientific research. Although microvascular decompression (MVD) in treatment resistant HTN is not a standard procedure, it can be discussed in selected patients with intractable severe HTN.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cranial nerves; Image fusion; Image processing; MRI; Posterior fossa; Vascular compression disorders

Classification of neurovascular compression in glossopharyngeal neuralgia: Three-dimensional visualization of the glossopharyngeal nerve - Tanrikulu, Levent; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Surgical Neurology International, 2015)
Background: We introduce a method of noninvasive topographical analysis of the neurovascular relationships of the glossopharyngeal nerve (CN IX) by three-dimensional (3D) visualization. Patients with glossopharyngeal neuralgia (GN) resulting from neurovascular compression (NVC) were studied. Methods: 15 patients with GN were prospectively examined with 3D visualization using high-resolution magnetic resonance imaging with constructive interference in steady state (MR-CISS). The datasets were segmented and visualized with the real, individual neurovascular relationships by direct volume rendering. Segmentation and 3D visualization of the CN IX and corresponding blood vessels were performed. The 3D visualizations were interactively compared with the intraoperative setup during microvascular decompression (MVD) in order to verify the results by the observed surgical-anatomical findings. Results: 15 patients (female/male: 5/10) were examined. All of them underwent MVD (100%). Microvascular details were documented. The posterior inferior cerebellar artery (PICA) was the most common causative vessel in 12 of 15 patients (80%), the vertebral artery (VA) alone in one case (6.7%), and the combination of compression by the VA and PICA in 3 patients (13.3%). We identified three distinct types of NVC within the root entry zone of CN IX. Conclusion: 3D visualization by direct volume rendering of MR-CISS data offers the opportunity of noninvasive exploration and anatomical categorization of the CN IX. It proves to be advantageous in supporting to establish the diagnosis and microneurosurgical interventions by representing original, individual patient data in a 3D fashion. It provides an excellent global individual view over the entire neurovascular relationships of the brainstem and corresponding nerves in each case.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Classification; glossopharyngeal nerve; glossopharyngeal neuralgia; image processing; neurovascular compression

Comparing 1.5 T and 3.0 T MR data for 3D visualization of neurovascular relationships in the posterior fossa - Hastreiter, Peter; Maliachova, Olga; Fahlbusch, Rudolf; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Acta Neurochirurgica, 2023)
Background: Neurovascular relationships in the posterior fossa are more frequently investigated due to the increasing availability of 3.0 Tesla MRI. For an assessment with 3D visualization, no systematic analyzes are available so far and the question arises as to whether 3.0 Tesla MRI should be given preference over 1.5 Tesla MRI. Methods: In a prospective study, a series of 25 patients each underwent MRI investigations with 3D-CISS and 3D-TOF at 1.5 and 3.0 Tesla. For both field strengths separately, blood vessel information from the TOF data was fused into the CISS data after segmentation and registration. Four visualizations were created for each field strength, with and without optimization before and after fusion, which were evaluated with a rating system and verified with the intraoperative situation. Results: When only CISS data was used, nerves and vessels were better visualized at 1.5 Tesla. After fusion, flow and pulsation artifacts were reduced in both cases, missing vessel sections were supplemented at 3.0 Tesla and 3D visualization at 1.5 and 3.0 Tesla led to anatomically comparable results. By subsequent manual correction, the remaining artifacts were further eliminated, with the 3D visualization being significantly better at 3.0 Tesla, since the higher field strength led to sharper contours of small vessel and nerve structures. Conclusion: 3D visualizations at 1.5 Tesla are sufficiently detailed for planning microvascular decompression and can be used without restriction. Fusion further improves the quality of 3D visualization at 3.0 Tesla and enables an even more accurate delineation of cranial nerves and vessels.
CRIS-Team Scopus Importer:2023-12-29
Keywords: 1.5 and 3.0 Tesla; 3D Visualization; Compression syndromes; Data fusion; Neurovascular relationships; Posterior fossa

Data fusion and 3D visualization for optimized representation of neurovascular relationships in the posterior fossa - Hastreiter, Peter; Bischoff, Barbara; Fahlbusch, Rudolf; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Acta Neurochirurgica, 2022)
Background: Reliable 3D visualization of neurovascular relationships in the posterior fossa at the surface of the brainstem is still critical due to artifacts of imaging. To assess neurovascular compression syndromes more reliably, a new approach of 3D visualization based on registration and fusion of high-resolution MR data is presented. Methods: A total of 80 patients received MRI data with 3D-CISS and 3D-TOF at 3.0 Tesla. After registration and subsequent segmentation, the vascular information of the TOF data was fused into the CISS data. Two 3D visualizations were created for each patient, one before and one after fusion, which were verified with the intraoperative situation during microvascular decompression (MVD). The reproduction quality of vessels was evaluated with a rating system. Results: In all cases, the presented approach compensated for typical limitations in the 3D visualization of neurovascular compression such as the partial or complete suppression of larger vessels, suppression of smaller vessels at the CSF margin, and artifacts from heart pulsation. In more than 95% of the cases of hemifacial spasm and glossopharyngeal neuralgia, accurate assessment of the compression was only possible after registration and fusion. In more than 50% of the cases with trigeminal neuralgia, the presented approach was crucial to finding the actually offending vessel. Conclusions: 3D visualization of fused image data allows for a more complete representation of the vessel-nerve situation. The results from this approach are reproducible and the assessment of neurovascular compression is safer. It is a powerful tool for planning MVD.
CRIS-Team Scopus Importer:2022-01-21
Keywords: 3D visualization; Compression syndromes; Data fusion; Neurovascular relationships; Posterior fossa

High-Resolution 3D-constructive interference in steady-state MR imaging and 3D time-of-flight MR angiography in neurovascular compression: A comparison between 3T and 1.5T - Dörfler, Arnd; Garcia, M.; Naraghi, Ramin; Zumbrunn, T.; Roesch, J.; Hastreiter, Peter (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: High-resolution MR imaging is useful for diagnosis and preoperative planning in patients with NVC. Because high-field MR imaging promises higher SNR and resolution, the aim of this study was to determine the value of high-resolution 3D-CISS and 3D-TOF MRA at 3T compared with 1.5T in patients with NVC. MATERIALS AND METHODS: Forty-seven patients with NVC, trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia were examined at 1.5T and 3T, including high-resolution 3D-CISS and 3D-TOF MRA sequences. Delineation of anatomic structures, overall image quality, severity of artifacts, visibility of NVC, and assessment of the SNR and CNR were compared between field strengths. RESULTS: SNR and CNR were significantly higher at 3T (P < .001). Significantly better anatomic conspicuity, including delineation of CNs, nerve branches, and assessment of small vessels, was obtained at 3T (P < .02). Severity of artifacts was significantly lower at 3T (P < .001). Consequently, overall image quality was significantly higher at 3T. NVC was significantly better delineated at 3T (P < .001). Six patients in whom NVC was not with certainty identifiable at 1.5T were correctly diagnosed at 3T. CONCLUSIONS: Patients with NVC may benefit from the higher resolution and greater sensitivity of 3T for preoperative assessment of NVC, and 3T may be of particular value when 1.5T is equivocal.
CRIS-Team Scopus Importer:2022-08-05

Neurovascular compression in arterial hypertension: Correlation of clinical data to 3d-visualizations of mri-findings - Manava, Panagiota; Hastreiter, Peter; Schmieder, Roland; Jung, Susanne; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael; Buchfelder, Michael; Naraghi, Ramin (Open Neuroimaging Journal, 2021)
Aims: In this study, we attempted to identify clinical parameters predicting the absence or presence of Neurovascular Compression (NVC) at the Ventrolateral Medulla (VLM) in arterial hypertension (HTN) in MRI findings. Background: Cardiovascular and pulmonary afferences are transmitted through the left vagus and glossopharyngeal nerve to the brain stem and vasoactive centers. Evidence supports the association between HTN and NVC at the left VLM. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left VLM. Image processing of MRI provides comprehensible detection of NVC. HTN affects hemodynamic parameters and organs. Objective: This study analyzes and correlates clinical data and MRI findings in patients with and without NVC at the VLM in treatment resistant HTN to obtain possible selection criteria for neurogenic hypertension. Methods: In 44 patients with treatment resistant HTN, we compared MRI findings of neurovascular imaging to demographic, clinical and lifestyle data, office and 24-hour ambulatory Blood Pressure (BP), and cardiovascular imaging and parameters. Results: Twenty-nine (66%) patients had evidence of NVC at the VLM in MRI. Sixteen patients (36%) had unilateral NVC on the left side, 7 (16%) unilateral right and 6 (14%) bilateral NVC. Fifteen (34%) had no evidence of NVC at the VLM. Patients with left sided NVC were significantly younger, than those without NVC (p=0.034). They showed a statistically significant variance in daytime (p=0.020) and nighttime diastolic BP (p<0.001) as the mean arterial pressure (p=0.020). Other measured parameters did not show significant differences between the two groups. Conclusion: We suggest to examine young adults with treatment resistant HTN for the presence of NVC at VLM, before signs of permanent organ damage appear. Clinical and hemodynamic parameters did not emerge as selection criteria to predict NVC. MVD as a surgical treatment of NVC in HTN is not routine yet as a surgical treatment of NVC in HTN is not routine yet. Detection of NVC by imaging and image processing remains the only criteria to suggest MVD, which should be indicated on an individual decision.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypertension; Image fusion; MRI; Neuroimaging; Neurovascular compression; Ventrolateral medulla

Neurovascular compression of medulla oblongata - Association for gestation-induced hypertension - Tanrikulu, Levent; Naraghi, Ramin; Ernst, Veronika; Voigt, Franziska; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Beckmann, Matthias; Goecke, Tamme W. (Medical Hypotheses, 2015)
Patients with essential hypertension may show neurovascular compression (NVC) at the rostral ventrolateral medulla oblongata (RVLM). Ectatic loops of the vertebral artery (VA) or the inferior posterior cerebellar artery (PICA) cause NVC. This study aims to show the existence and morphology of NVC in patients with gestation-induced hypertension. 17 females were prospectively examined between 19. +. 0 and 35. +. 6. weeks of gestation. 3 patients with chronic hypertension (group A), 10 patients with preeclampsia (group B), 3 patients with superimposed preeclampsia (chronic hypertension with preeclampsia; group C) and one normotensive patient were included. Groups B and C represented patients with gestation-induced hypertension. All 17 patients underwent imaging by high resolution magnetic resonance imaging (MR-CISS, constructive interference in the steady state). Image processing was done with segmentation and three-dimensional (3D)-visualization was implemented with direct volume rendering of the individual neurovascular details of each patient. 9 of 17 patients (53%) showed NVC of the RVLM. Right-sided NVC was seen in 7 patients (41%). Left-sided NVC was seen in 6 patients (35%). Bilateral NVC was seen in 4 patients (24%). NVC was missing in 8 of the examined 17 patients (47%). The existence of NVC with high-resolution MRI was analyzed in gestation-induced hypertensive pregnant females for the first time. Neurovascular conflicts were seen in hypertensive pregnants. It is possible that NVC is potentially associated in patients with gestation-induced hypertension.
CRIS-Team Scopus Importer:2022-08-05

Phase-amplitude coupling measures for determination of the epileptic network: A methodological comparison - Ali, Ryshum; Gollwitzer, Stephanie; Reindl, Caroline; Hamer, Hajo; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael; Hastreiter, Peter; Rampp, Stefan (Journal of Neuroscience Methods, 2022)
CRIS-Team WoS Importer:2022-05-13
Keywords: EEG; Epilepsy; Phase-Amplitude Coupling

The SIP-NVC-Wizard User Guidance on Segmentation for Surgical Intervention Planning of Neurovascular Compression - Franz, Daniela; Syré, Liane; Paulus, Dietrich; Bischoff, Barbara; Wittenberg, Thomas; Hastreiter, Peter (Deutschland, 2015)
Neurovascular compression syndromes (NVC) result from a compression of the entry/exit zone of cranial nerves by a vessel at the surface of the brainstem. Surgical intervention planning (SIP) for NVC enables a comprehensive spatial understanding of the patient specific anatomy. Specifically, brainstem, vessels and nerves are segmented in NVC SIP. To support segmentation for NVC SIP, we propose a wizard-based user guidance. The SIP-NVC-Wizard guides the user through the patient's individual anatomy and segmentations, and translates the parameter tuning into adequate medical terminology. We were able to show pathological nerve-vessel-contact in ten NVC cases producing results comparable to conventional NVC SIP, and performed a pilot-study to evaluate usability and functionality of the proposed wizard. With the SIP-NVC-Wizard our subjects were able to perform a NVC SIP without any knowledge in image processing. Anatomical beginners showed a steep learning curve. Time was reduced to 34 minutes compared to 1-2 hours for conventional NVC SIP.